UPAYA PREVENTIF DALAM MENANGANI BAHAYA PORNOGRAFI BAGI PELAJAR DENGAN MEDIA VISUAL POSTER - Dini, Meza Fitri; Fauziah, Annisa; Prama, Shafa Salsabillah; Puadah, Popi (Journal Education and Government Wiyata, 2024)
The dangers of pornography in the digital era have become an increasingly deep issue, requiring effective prevention strategies. This research aims to investigate the role of posters in social campaigns as an effort to prevent the dangers of pornography. The research method used is a literature study which includes searching for sources in academic databases, digital libraries and other trusted sources of information. The selected literature sources involve scientific articles, books, research reports, and official publications related to the concept of preventing the dangers of pornography and the role of posters in social campaigns. This research aims to identify key findings regarding the effectiveness of prevention campaigns involving the use of posters. Findings from the literature were organized and analyzed to understand campaign strategies, the role of posters in conveying prevention messages, and their impact on community awareness and behavior, especially in the school environment. The results of this literature research reveal that posters can be a powerful tool in educating students about the dangers of pornography. Posters not only convey clear information about negative impacts, but can also stimulate active participation in prevention efforts. These findings provide a theoretical basis for further research, including empirical research involving the community, parents and educators as respondents.